2008
DOI: 10.1063/1.2937835
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated emission from trap electronic states in oxide of nanocrystal Si

Abstract: We have demonstrated a stimulated photoluminescence (PL) at 694 and 692nm whose emission peak has a Lorentzian shape with a full width at half maximum of 0.5–0.6nm. This stimulated emission comes from the nanostructures on porous silicon oxidized fabricated by irradiation and annealing treatment. Controlling the time of annealing can produce a good coherent emission. A model has been proposed for explaining the stimulated emission in which the trap states of the interface between oxide of silicon and porous na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…A schematic diagram showing oxide formation on pore walls and their corresponding localized states formation due to Si-O-Si bonds are shown in Figure 6. The present observation of the red shift in PL peak position on thermal annealing are in agreement with the theoretical model about the trap electronic states in nanocrystal Si reported by Huang et al [39].…”
Section: Photoluminescence Appearance In Pssupporting
confidence: 93%
See 1 more Smart Citation
“…A schematic diagram showing oxide formation on pore walls and their corresponding localized states formation due to Si-O-Si bonds are shown in Figure 6. The present observation of the red shift in PL peak position on thermal annealing are in agreement with the theoretical model about the trap electronic states in nanocrystal Si reported by Huang et al [39].…”
Section: Photoluminescence Appearance In Pssupporting
confidence: 93%
“…They have attributed their observation to the hybrid model in which both quantum confinement and luminescence centres outside the nanoscale unit has been accounted [38]. Recently Huang et al have reported theoretical calculation where they showed that the trap electronic states appear in the energy gap of the smaller nanocrystal Si on thermal annealing when Si=O bonds or Si-O-Si bonds are formed [39]. In the present study, the red shift in PL peak of PS can be understood as follows.…”
Section: Photoluminescence Appearance In Psmentioning
confidence: 55%
“…C acts as the donor because its electronegativity is greater than that of Si. For the C-rich surface (Figure 4 b), the behavior is similar; however, the principal contribution to the states near the VBM is from the O atoms in conjunction with the C atoms, which leads us to believe that these trap-like states are caused by the C-O-C bonds at the surface of the pores [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…But the wavelength of PL emission stands at some fixed positions for smaller Si QDs prepared in oxygen, nitrogen, or air atmospheres. 7,8 Numerous models have been proposed to explain the change of the PL, Wolkin et al indicated that the disappearing of the blue-shifting is related to the trapping of an electron by Si ¼ O bond that produces localized levels in the bandgap of nanocrystals smaller than 3 nm, which was argued because no any Si ¼ O bond has been detected in FTIR transmission spectra. 9 Hadjisavvas et al found that the shape of larger nanocrystals is often observed to be faceted, while that of smaller ones is always found to be spherical.…”
mentioning
confidence: 99%